Moral Intelligence: Construction of a Moral Intelligence Scale Developed in Poland - Dacka, Monika (Journal of religion and health, 2025)
Moral intelligence is the ability to distinguish between right and wrong, to make ethical decisions, and to be guided by certain values in life. In view of cultural and social change and the ongoing crisis of values, moral intelligence is of particular importance today in various areas of human life and function. The purpose of this article is to introduce the topic of moral intelligence and its operationalization in order to construct the moral intelligence scale. The psychometric properties of the tool were also assessed. It was carried out in three stages. The first involved the creation of items based on the concept of moral intelligence. Next, exploratory factor analysis was conducted on a Polish sample of 433 people (218 women, 215 men; M = 27.23 years; SD = 4.66). In the third, the confirmatory factor analysis conducted on a Polish sample of 643 individuals (339 females, 304 males; M = 29.03 years; SD = 4.34) confirmed the five factors of the Moral Intelligence Scale. Moral intelligence has a specific structure. Analyses have shown that it is a complex construct consisting of five factors that have been recognized as: responsibility, honesty, forgiveness, conscience, and compassion.